KONTRIBUSI MOTIVASI BELAJAR TERHADAP HASILBELAJAR ASKEB IV PATOLOGI MAHASISWA TINGKAT III SEMESTER IV PRODI D III KEBIDANAN STIKes PRIMA NUSANTARA BUKITTINGGI TAHUN 2013 - Tuti Oktriani, Tuti Oktriani; Wiwit Fetrisia, Wiwit Fetrisia (LPPM Universitas Prima Nusantara Bukittinggi, 2013)
Immediate mobilization gradually very useful for the process of wound healing and prevent infection and thrombosis vena.bila too early mobilization may affect wound healing. Only a small proportion of mothers post partum section Caesarea early mobilization after 6-24 hours post-surgery, the mother who does not want to do early mobilization is caused by several reasons, including the mother feels fear and pain. Therefore, early mobilization is the first step toward accelerating the wound healing process Caesarea mothers with post section. This study was conducted to determine the effectiveness of early mobilization in the capital section post Caesarea to accelerate the wound healing process Caesarea section. This type of pre-experimental research design with posttest only control group design. Total sample of 15 respondents conducted by accidental sampling. Analysis of studies using T test Test. From the analysis of early mobilization in the capital section post Caesarea on wound healing by using T test Test results obtained p value = 0.000 where the value of p